The Sciences of The Qur'an and Their Development Until Now - Tiara Gita Safitri; Ali Akbar; Selfa Nur Ummi; Vera Seftia (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. Ul?mul-Qur'?n, the sciences of the Qur'an, encompass various fields related to the study of the Qur'an, including its revelation, composition, miraculous aspects, explanations of difficult terms, and interpretation. Understanding the historical and thematic development of Ul?mul-Qur'?n is essential for appreciating its role in Islamic scholarship and its evolution over time. Purpose. This research aims to examine the development of Ul?mul-Qur'?n from its inception to the present, highlighting key phases and contributions that have shaped its current understanding. Method. The study uses a qualitative research method with a literature-based approach. Data were gathered from books, textbooks, and scholarly articles on Ul?mul-Qur'?n, enabling an in-depth exploration of relevant themes. Analysis involved categorization and pattern identification to form a comprehensive understanding of Ul?mul-Qur'?n’s evolution. Results. The study identifies several distinct phases in the development of Ul?mul-Qur'?n, including the period of the Prophet Muhammad (Sallallahu 'alaihi wa sallam), the Caliphate, the Companions and Tabi'in (Followers), the Tadwin (Compilation) Period, and the Modern/Contemporary Period. Each phase reflects unique contributions and evolving perspectives on Qur'anic sciences, shaped by historical and cultural contexts. Conclusion. This research concludes that Ul?mul-Qur'?n has developed through multiple stages, each adding depth and sophistication to its study. The phases illustrate how Qur'anic sciences have been influenced by historical periods and intellectual movements, continuing to evolve in response to modern scholarly needs. The study highlights the importance of ongoing research and documentation to support further development and accessibility of Ul?mul-Qur'?n in contemporary scholarship.